2009
DOI: 10.1111/j.1528-1167.2009.02178.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure frequency and sex steroids in women with partial epilepsy on antiepileptic therapy

Abstract: SUMMARYPurpose: Neuroactive sex steroids influence neuron excitability, which is enhanced by estradiol (E2) and decreased by progesterone (Pg). In epilepsy, the production, metabolism, biologic availability, and activity of sex hormones may be affected by seizures themselves or by antiepileptic drugs (AEDs). This cross-sectional observational study was aimed at evaluating the relationships between sex steroids, seizure frequency, and other clinical parameters in women with partial epilepsy (PE) on AED treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…56 Several other reports invoke the role of hormones as a contributor to seizure occurrence and cyclic seizure patterns, including the seizure risk imparted by anovulatory cycles, in women with epilepsy. 5759 Therefore, both oestrogen and progesterone cycling have been associated with patterns of seizure occurrence in catamenial epilepsy.…”
Section: Endogenous Hormones and Catamenial Epilepsymentioning
confidence: 99%
“…56 Several other reports invoke the role of hormones as a contributor to seizure occurrence and cyclic seizure patterns, including the seizure risk imparted by anovulatory cycles, in women with epilepsy. 5759 Therefore, both oestrogen and progesterone cycling have been associated with patterns of seizure occurrence in catamenial epilepsy.…”
Section: Endogenous Hormones and Catamenial Epilepsymentioning
confidence: 99%
“…In spite of the previously reported relationship between hormones and seizure propensity, the presence of complex hormonal exophenotypes was not associated with epilepsy in our cohort ( W = 274, unadj. p = 0.3742) [ 32 ]. However, despite the small number of women reporting epilepsy ( N = 7), epilepsy shared a modest positive relationship with the number of immune-mediated disorders irrespective of the group ( W = 166, unadj.…”
Section: Resultsmentioning
confidence: 99%
“…Murialdo et al (22), (2009) found patients with more severe disease showed more relevant changes in their sex hormone profile and impaired progesterone levels during the luteal phase. Pack (23) reported that women with epilepsy have a higher than expected prevalence of sexual and reproductive dysfunction, the epilepsy syndrome and localization influence the presentation of these dysfunctions and specific AED influence the presentation of reproductive dysfunction.…”
Section: Discussionmentioning
confidence: 99%